SPATIAL EVOLUTION OF SMART CITIES FOR SUSTAINABLE TOURISM: A CASE STUDY OF PHUKET PROVINCE, THAILAND - Komsan KIRIWONGWATTANA; Katawut WAIYASUSRI (Geo Journal of Tourism and Geosites)
In this research, the objective is to study the Spatial Evolution of Smart Cities for Sustainable Tourism in Phuket Province, Thailand from 2005-2024, using the Geo-informatic Technique as information for decision-making in determining the direction of Smart City. The study results found that land use patterns such as Urban and built-up land, Waterbodies, and Forest land have had an increasing trend over the past 20 years. In 2005, Urban and built-up land was found to cover 132.19 km2 (24.10% of the total area). In 2024, it was found to have greatly increased, covering 165.91 km2 (30.25% of the total area), especially in Thalang District, which is north of Phuket. The area has a wide plain landscape, and beautiful wide beaches such as Bang Tao Beach. There has been a change from agricultural land to housing developments, residential areas, restaurants, hotels, resorts and homestays. The results of this study have been prepared as a spatial database for supporting decision-making in monitoring and planning the development of areas to support the expansion of sustainable tourism in the future to become a smart city.